Comparative study of mesopourous silica obtained by different synthetic routes to improve the analysis of Cu(II) in sugar cane spirit - Lima, Jéssica Brito dos Santos; de Carvalho, Sanny Wedja Melo Machado; Andrade, Paula de Cássia; Silva, Jonatas de Oliveira Souza; Santos, Ewerton; Santos, Danilo Oliveira; Alexandre, Marcelo da Rosa; Sussuchi, Eliana Midori (Scientia Plena, 2020)
Mesoporous silicas have properties that allow their wide chemical application, due to the large amount of silanol groups on their walls. The possibility of introducing functional groups inside and on the surface of their pores becomes viable the use of these functionalized mesoporous materials for the adsorption of metal ions. Cooper ions are essential for vital functions, but in high concentrations, they are responsible for causing problems to the human organism. Therefore, it is important to monitor the species in different media, such as sugar cane spirit. Mesoporous materials type MCM-41 functionalized were obtained by three different methods using direct (in situ) and indirect (post-synthesis) routes. The mesoporous materials have exhibited properties according to the IUPAC classification. Modified carbon paste electrodes (MCPEs) were prepared by immobilizing the synthesized materials for Cu2+ analysis. The modified electrode obtained by the immobilization of functionalized mesoporous R2 (MCPE/R2) presented the best sensitivity for Cu2+ detection. Under optimum experimental conditions, the MCPE/R2 exhibited a linear range in between 0.99 and 11.80 μmol L-1, a sensitivity based on the Limit of Detection (LOD) of 0.50 μmol L-1and Limit of Quantification (LOQ) of 0.99 μmol L-1, precision (DPRmáx) equals to 10.6% and recovery of 92.2%. The developed method proved to be efficient for Cu2+ determination in sugar cane spirit and the accuracy of the results were comparable to those obtained by AAS.